A Comparison of the Legal Process for Determining Suspects in Corruption Cases in Indonesia and Thailand - Siregar, Mohammad Haikal Athallah; Abduh, Rachmad (Al-Risalah, 2026)
Corruption is an extraordinary crime with serious implications for state stability, social justice, and public trust, requiring effective legal mechanisms that also safeguard human rights. A crucial stage in corruption law enforcement is the determination of suspects, as it initiates formal legal proceedings and carries significant legal consequences. This study analyzes and compares the mechanisms for determining suspects in corruption cases in Indonesia and Thailand, as well as the role of specialized institutions in each system. Using normative legal research with statutory and comparative approaches, this study examines primary, secondary, and tertiary legal materials through qualitative analysis. The findings show that Indonesia applies a formal procedural mechanism under the Criminal Procedure Code (KUHAP), combined with judicial oversight through pretrial review to protect suspects’ rights. In contrast, Thailand centralizes authority in the National Anti-Corruption Commission (NACC) through a preliminary inquiry mechanism that prioritizes institutional effectiveness but provides limited judicial oversight at the early stage. These differences reflect distinct legal policy choices in balancing anti-corruption effectiveness and human rights protection. This study highlights the trade-off between procedural safeguards and institutional efficiency in the two systems.